Batch and Flow Injection Spectrophotometric Determination of Tetracycline Hydrochloride and Doxycycline Hyclate in Pharmaceutical Preparations - Q. Al-Abachi, Mouayed; A. Al-Nedawi, Zaid (Iraqi Journal of Science, 2023)
New, simple and accurate batch and flow injection spectrophotometricmethods have been developed for the determinationsof tetracyclinehydrochloride (TCH) and doxycycline hyclate (DCH) in pharmaceuticalpreparations. The methods are based on diazotization ofmetchlopramide and coupling reaction with either TCH or DCH in alkalinemedium to form yellow–orange water soluble dye with absorption maximaat 414 and 436 nm for TCH and DCH, respectively. A graphs of absorbanceversus concentration show that Beer’s law was obeyed over theconcentration ranges of 1 –52 μgmL-1 TCH and DCH for batch method andof 8 – 240 μg mL-1 TCH and 5 – 350 μgmL-1 DCH for FIA method. Thelimits of detection in batchmethods were 0.333 and 0.235μgmL-1for TCHand DCH respectively, and in FIA methods were 0.895, 0.612 μgmL-1forTCH and DCH respectively. Samplethroughputs in FIA procedures were 120and 80samples per hour for TCH and DCH, respectively. Different chemicaland physical experimental parameters affecting on the development andstability of the colored product were carefully studied and the proposedmethods were successfully applied for determination of TCH and DCH inpharmaceutical preparations.